Angiopoietin 2 and Neuropeptide Y are Associated with Diabetic Kidney Disease in Type 1 Diabetes Mellitus - Sokolovska, Jelizaveta; Stefanovics, Juris; Gersone, Gita; Pahirko, Leonora; Valeinis, Janis; Kalva-Vaivode, Sanita; Rovite, Vita; Blumfelds, Leons; Pirags, Valdis; Tretjakovs, Peteris (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Serum angiopoietin 2 levels have been associated with endothelial dysfunction and diabetic kidney disease. Derangements in autonomous nervous system lead to increased production of vasoconstrictory and angiogenic mediators such as norepinephrine and neuropeptide Y and are associated with increased risk of microvascular complications.Aim To investigate associations between angiopoietin 2, neuropeptide Y and diabetic kidney disease in patients with type 1 diabetes mellitus.Methods 289 patients with type 1 diabetes mellitus duration > 1 year were included. Patients were stratified according to presence of diabetic nephropathy (macroalbuminuria, estimated glomerular filtration rate<60 ml/min/1.73 m2 or end-stage renal disease). Angiopoietin 2 was measured by Luminex technology. Neuropeptide Y was measured by ELISA.Results Patients with diabetic nephropathy had significantly increased levels of angiopoietin 2 (4020.5 (2172.4–5778.1) pg/ml vs. 2001.0 (1326.7–2862.7) pg/ml) and neuropeptide Y (18.22 (14.85–21.85) ng/ml vs. 12.91 (9.96–17.07) ng/ml). Higher levels of angiopoietin 2 and neuropeptide Y were observed also in patients with arterial hypertension. Angiopoietin 2 and neuropeptide Y correlated significantly (ρ=0.245, p<0.001). Both biomarkers were significant predictors of estimated glomerular filtration rate and diabetic nephropathy in univariate regression models. In the fully adjusted regression models and after application of a stepwise selection regression method, angiopoietin 2 demonstrated a stronger predictive power for diabetic nephropathy compared to neuropeptide Y.Conclusion Diabetic nephropathy is associated with increased serum concentrations of angiopoietin 2 (marker of endothelial dysfunction) and neuropeptide Y (marker of sympathetic activity) in type 1 diabetes. Angiopoietin 2 is a more potent predictor of diabetic nephropathy compared to neuropeptide Y.
Keywords: type 1 diabetes; diabetic nephropathy; arterial hypertension; estimated glomerular filtration rate; endothelial dysfunction, autonomic neuropathy